2009
DOI: 10.1158/0008-5472.can-09-0487
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α and Interleukin-1 Antagonists Alleviate Inflammatory Skin Changes Associated with Epidermal Growth Factor Receptor Antibody Therapy in Mice

Abstract: Cancer patients receiving epidermal growth factor receptor (EGFR) antibody therapy often experience an acneiform rash of uncertain etiology in skin regions rich in pilosebaceous units. Currently, this condition is treated symptomatically with very limited, often anecdotal success. Here, we show that a monoclonal antibody targeting murine EGFR, ME1, caused a neutrophil-rich hair follicle inflammation in mice, similar to that reported in patients. This effect was preceded by the appearance of lipid-filled hair f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…All of these findings have also been observed in our analyzed samples. These findings have also been shown in mice treated with an anti-EGFR monoclonal antibody, where follicular plugging with increased sebaceous gland size and a neutrophilic follicular infiltrate are observed (22). Enlargement of sebaceous units was not detected in our patients, which could potentially relate to timing of biopsies.…”
Section: Cetuximabsupporting
confidence: 80%
See 1 more Smart Citation
“…All of these findings have also been observed in our analyzed samples. These findings have also been shown in mice treated with an anti-EGFR monoclonal antibody, where follicular plugging with increased sebaceous gland size and a neutrophilic follicular infiltrate are observed (22). Enlargement of sebaceous units was not detected in our patients, which could potentially relate to timing of biopsies.…”
Section: Cetuximabsupporting
confidence: 80%
“…There is also some evidence that these agents may also alter the immune system (21). More recently, a preclinical model showed the role of tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1) in the development of HER1i-associated skin rash and suggested a possible therapeutic role for anti-TNF agents (22). Several studies have aimed to identify histologic and immunohistochemical features of skin in patients undergoing therapy with HER1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of the skin toxicity secondary to EGFR inhibitors has until recently been mostly empirical, consisting of the use of topical skin moisturizers, topical sunscreens, and topical and systemic anti-inflammatory agents and antibiotics (32)(33)(34). The use of topical steroids and immunosuppressant agents has not been clearly shown to be of clinical value.…”
Section: Introductionmentioning
confidence: 99%
“…We tested IL-1R blockade as an approach to protecting Fancc -/-mice from bone marrow failure during repeated emergency granulopoiesis challenge. We used an IL-1R antagonist (anakinra) that is FDA approved for human subjects with autoimmune disorders and has been previously used in murine models (43,49). We found that treatment with anakinra blocked emergency granulopoiesis in WT mice and ameliorated bone Stable transfectants.…”
Section: Murine Studiesmentioning
confidence: 99%